2018
DOI: 10.1021/acsenergylett.8b01409
|View full text |Cite
|
Sign up to set email alerts
|

Electroreduction of CO2 to CO on a Mesoporous Carbon Catalyst with Progressively Removed Nitrogen Moieties

Abstract: In this study, we prepared nitrogen-removed mesoporous carbon (NRMC) catalysts by applying various heat treatments to nitrogen-doped mesoporous carbon (NMC), which were applied as novel electrocatalysts for CO 2 reduction reaction (CO 2 RR). With the nitrogen moieties being progressively removed, the NRMC catalysts exhibited enhanced CO generation from CO 2 RR, whereas the competing hydrogen evolution reaction (HER) has been suppressed. Through suitable annealing treatment, the defect-rich NRMC catalyst is abl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
96
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 147 publications
(101 citation statements)
references
References 36 publications
5
96
0
Order By: Relevance
“…Nevertheless, the MnNPC‐1000 exhibits larger surface area (1209 m 2 g −1 ) and total volume of pores (0.37 cm 3 g −1 ), with the average diameter is reduced from 7.48 nm (MnNPC‐900) to 6.88 nm (Table S2, Supporting Information). These results are likely caused by the removal of N species from the MnNPC‐1000 at high‐temperature thermal‐treatments, leaving numerous defects in the samples …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, the MnNPC‐1000 exhibits larger surface area (1209 m 2 g −1 ) and total volume of pores (0.37 cm 3 g −1 ), with the average diameter is reduced from 7.48 nm (MnNPC‐900) to 6.88 nm (Table S2, Supporting Information). These results are likely caused by the removal of N species from the MnNPC‐1000 at high‐temperature thermal‐treatments, leaving numerous defects in the samples …”
Section: Methodsmentioning
confidence: 99%
“…Based on these results, we believe that the Mn–N x species can be generated at 800 °C, but the majority of P atoms still stay as phosphate groups rather than P dopants in the MnNPC‐800. On the other hand, although the P dopants are well‐formed at 1000 °C, the total nitrogen content in the doped carbon is also reduced (see Table S1 in the Supporting Information), especially the N of Mn–N x species . As a result, the MnN x P y complex can hardly be formed in either the MnNPC‐800 or the MnNPC‐1000 catalysts.…”
Section: Methodsmentioning
confidence: 99%
“…Indeed, the results with the Ni hybrid catalysts offer a unique perception into the prospect of tuning inactive catalysts for CO 2 RR into high performing catalysts. Very recently, we demonstrated that by encapsulating Ni nanoparticles within a graphitic carbon shell, we are able to attain very high FE CO that is maintained even in the presence of electrolyte purities . Similarly, Cu nanoparticles dispersed on CNT support is shown to enhance methanol production with reported 38.5% FE at −1.1 V whereas metallic Cu is known to produce minuscule levels of methanol .…”
Section: Active Sites In Metal‐carbon Catalystsmentioning
confidence: 95%
“…The strategies to generate intrinsic lattice defects, such as point defect, atom/ion vacancy, dislocations, grain boundaries, and stepped surfaces have been widely investigated in CO 2 RR application. These parameters and densities can be tailored by treatments such as doping, thermal treatment in a reductive or oxygen‐deficient environment, introduction of metal/metal oxide interfaces, plasma treatment, and light illumination . Introduction of defects can enhance the number of active sites available for electrochemical reactions and hence increase the catalyst efficiency.…”
Section: Active Sites In Metal‐based Catalystsmentioning
confidence: 99%
See 1 more Smart Citation